The Relationship between Knowledge and Attitudes of Students About Genetalia Hygiene and Leucorrhoea at Al-Ansor High School, Kec. Bandar Kab. Simalungun Year 2020 - Kamaliah Ainun (Science Midwifery, 2020)
Whitish or often called Flour Albus is a normal vaginal secretion in women. In normal circumstances, a healthy vagina produces fluid to clean the vagina from unwanted foreign objects. The aim of this research is to determine the relationship between knowledge and attitudes of students about genetalia hygiene with the incidence of vaginal discharge in SMA Al-Ansor Kec. Bandar Kab. Simalungun in 2020. This research uses a quantitative research type, with a cross-sectional design. This research design uses a cross-sectional design. The population in the study were all students at SMA Al-Ansor Kec. Bandar Kab. Simalungun in 2020 as many as 126 people, the sample in this study was 56 random sampling, with the research technique using the Chi Square test. The results of the research on the knowledge of students about genetic hygiene at Al-Ansor High School, the majority in the moderate category were 24 people (42.9%). The attitudes of students about genetic hygiene in SMA Al-Ansor Kec. Bandar Kab. Simalungun in 2020 the majority have positive attitudes as many as 30 people (53.6%), The incidence of vaginal discharge in Al-Ansor High School, Kec. Bandar Kab. In 2020, the majority of them experienced physiological vaginal discharge as many as 32 people (57.1%). The conclusion is that there is a significant relationship between the knowledge of students about genetalia hygiene with the incidence of vaginal discharge in SMA Al-Ansor Kec. Bandar Kab. Simalungun in 2020. There is a significant relationship between the attitudes of students about genetic hygiene with the incidence of vaginal discharge in SMA Al-Ansor Kec. Bandar Kab. Simalungun year 2020. Adolescent Reproductive Health counseling is recommended in relation to reproductive organs and how to maintain the health of the reproductive organs.